Pendugaan Tingkat Produktivitas Pertanian Lahan Kering dengan Metode Indeks Storie di Kecamatan Raya Kabupaten Simalungun - Apong Sandrawati; Arion Eudia Saragih Garingging (Soilrens, 2016)
The  aimed  of  this  research  was  to  find  out  the  level  of  agricultural  land  productivity  at  Raya SimalungunSubdistrict with Storie Index Method. This research had been done since March–May 2014 at Raya Simalungun Subdistrict. Sampling spot was done at the certain agricultural landused, slope, and types of soil. Land use types consist of dry land agriculture and plantation. The slopes consisted of land  with  vary  on  declivity;  2-15%,  15-25%,  25-40%  and  >40%,  meanwhile  the  soil’s  types  include Tropaquepts, Dystrandepts, Haplorthox, Tropudults, Hydrandepts. The result of agriculture land basedon several factors; dynamic factor of land such as drainage, erossion, pH, Electric Conductivity (EC) of soil layer, showed that the level of productivity of agricultural land in Raya Simalungun Subdistrict is Excellent  Quality,  Moderate,  Poor  and  Very  Poor.  The  most  extensive  land quality  is  at  Grade  3  orMedium quality is amounted to 21,109.85 Ha or 88.65% of the area of dry land agriculture. Area of productive dry  land  agriculture in Raya Simalungun Subdistrict is 22,059.40 Ha or 92,63% and  less productive land area is 1,754 Ha or 7.37 of area dry land agriculture. Key  words: Productivity  of agricultural  land,  storie index,  texture,  landuse,  drainage,  erossion,  pH, Electric   Conductivity (EC).